Analisis Media Pembelajaran IPAS Berbasis Crossword Puzzle Pada Materi Rantai Makanan Siswa Sekolah Dasar: Literatur Review - Teguh Handoyo; Umi Mahmudah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the urgency of crossword puzzle-based IPAS learning media that is effective in increasing student participation in the learning process in grade V elementary school. This method allows discussion in large and small groups, learners can participate in learning activities. Creating fun learning and making it easier for students to achieve learning goals both in cognitive, affective and psychomotor aspects. . This article uses the Systematic Literature Review (SLR) method to explore various studies related to the use of crossword puzzle-based IPAS learning media. Currently, there are many learning models introduced by each teacher in school. The development of education in Indonesia still does not educate students' creativity because schools only measure students' cognitive levels so that the level of creativity of students in Indonesia is low. Learning media using crossword puzzles is proposed as a solution to increase student creativity, especially in elementary school students. So this research has the aim of analyzing the benefits of crossword puzzles as a means of increasing student creativity. This analysis was carried out by collecting various sources of scientific literature related to the research variables. The results of the literature review research show that learning media using crossword puzzles can increase the creativity of elementary school students.